The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1111/j.1365-2621.1980.tb03862.x
|View full text |Cite
|
Sign up to set email alerts
|

Pentane Production as an Index Of. Rancidity in Freeze‐dried Pork

Abstract: Levels of hydrocarbon in the headspace over freeze-dried pork was measured to evaluate rancidity. At the same time, the -pork was given to a sensory panel to describe the degree of rancid odor. When the pentine level in the headspace reached about 0.05 ~1, 100% of the. panel described the pork as rancid. In the early stage of rancidity, the pentane production levels were not correlated with the rancid odor scores. However, overall pattern of the pentane production was significantly correlated with that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Measurement of pentane, another dominant breakdown product of linoleic acid, as an indicator of lipid oxidation in freeze-dried muscle foods was reported by Seo (1976) and Seo and Joel (1980). Bigalli (1977) showed that the pentane content relates well with the development of offflavours in several food systems.…”
Section: Hexanal and Other Carbonyl Compoundsmentioning
confidence: 95%
“…Measurement of pentane, another dominant breakdown product of linoleic acid, as an indicator of lipid oxidation in freeze-dried muscle foods was reported by Seo (1976) and Seo and Joel (1980). Bigalli (1977) showed that the pentane content relates well with the development of offflavours in several food systems.…”
Section: Hexanal and Other Carbonyl Compoundsmentioning
confidence: 95%
“…Pentane is another volatile marker of lipid oxidation (Seo and Joel 1980) and may be a more reliable measure of oxidation than the aldehydes due to its inert short-chain hydrocarbon structure, which does not undergo any further reactions (Loliger 1990). Pentane was the major volatile identified in each of the samples in this study.…”
Section: Volatile Analysismentioning
confidence: 99%
“…Measurement of some of the other breakdown products of autoxidation provides another promising approach to assessment of lipid oxidation. Using gas chromatographic (GC) analysis in conjunction with sensory panel evaluation, the most common volatiles measured as indicators of lipid oxidation have been hexanal, pentane, pentanal, heptanal, 2,4-decadienal, and 2,3-octanedione (Bailey et al, 1980;Cross and Ziegler, 1965;Dupuy et al, 1976;Fioriti et al, 1974;Fritsch and Gale, 1977;Reineccius, 1979;Ruenger et al, 1978;Seo and Joel, 1980;Shahidi et al, 1987;St. Angelo et al, 1987).…”
Section: Introductionmentioning
confidence: 99%